Istirātījiya ta’līmi al-insya’ fī markazi tabahhuri al-lugah al-arabiyah bi ma’hadi dāril al-lugah wal Karāmah Keraksaan Probolingo li al sanah 2022: The Strategy of Teaching Composition (al-Insyā’) at the Arabic Language Proficiency Center of Ma’had Dār al-Lughah wa al-Karāmah, Kraksaan Probolinggo, in the Year 2022 - Muqit, Abdul (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2022)
تعليم الإنشاء درس من دروس اللغة العربية وهو يلعب دورا مهما في تنمية مهارة اللغة العربية لاسيما في مهارة الكتابة ، واستراتيجية التعليم نشاط مختار اختاره المعلم لطلابه وهي أداة محتاجة في التعليم ، كما تنال أهداف التعليم المرادة فعالا . كذلك في تعليم الإنشاء ، على المعلم اختيار الاستراتيجية الجيدة لنجاح تعليمه . انطلاقا من خلفية البحث السابقة ،إشكالية البحث حيث يكون فيها المسألة الرئيسية ، وهي : كيف استخدام استراتيجية تعليم الإنشاء؟ والمسألة الفرعية وهي:ما مشکلات استخدام استراتيجية في تعليم الإنشاء؟ أما أهداف هذا البحث : لمعرفة كيفية استخدام استراتيجية تعليم الإنشاء و لمعرفة مشكلات استخدام استراتيجية تعليم الإنشاء. استخدم الباحثان المدخل الكيفي ونوع دراسة الحالة في هذا البحث . أما طريقة جمع البيانات التي استخدمتها الباحثانة هي الملاحظة والمقابلة والوثائقية . ثم طريقة تحليل البيانات بالتحليل التفاعلي لمالس وهوبرمان واختبار صحتها بتثليث المصادر وتثليث أدوات البحث . وأما النتائج التي حصلت عليها الباحثان من سؤالين سابقين هي : قد استخدمت معلمة الإنشاء في استراتيجية إنشاء الجملة من المفردة الجديدة وإنشاء القصة في الفئات والإنشاء على شكل المجلة الحائطية والتصويرية في تعليم الإنشاء . والمشكلات في استخدام استراتيجية تعليم الإنشاء تنقسم إلى ثلاث نواحي ؛ وهي المادة غير المخصوصة لتعليم الإنشاء، والمعلمة قد تغيب في التعليم، والطالبات منهن من فكرتها ضعيفة وإتقان مفرداتها قليل وفهم قواعدها ضعيف. Teaching al-Insyā’ (composition) is one of the lessons in Arabic language instruction and plays an important role in developing Arabic language skills, especially writing skills. A teaching strategy is a deliberate activity chosen by the teacher for the students and serves as an essential tool in the teaching process to achieve the intended educational objectives. Likewise, in teaching composition, the teacher must choose an effective strategy to ensure the success of the instruction. Based on the research background, the main problem of this study is: How is the strategy of teaching composition used? The sub-problem is: What are the difficulties in using strategies in teaching composition? The objectives of this study are to determine how the teaching strategy for composition is applied and to identify the problems encountered in using such strategies. The researchers used a qualitative approach with the case study method. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out using Miles and Huberman’s interactive analysis model, and the validity of the data was tested through source triangulation and method triangulation. The results obtained from the two research questions indicate that the composition teacher employed several strategies: sentence construction using new vocabulary, story creation in class groups, and wall magazine and visual composition activities in teaching composition. The problems encountered in implementing these strategies fall into three main areas: (1) teaching materials not specifically designed for composition instruction, (2) teacher’s occasional absence during lessons, and (3) students’ weak understanding of ideas, limited vocabulary mastery, and poor grasp of grammar.